Eric Mendelsohn and Tel Aviv - Ita Heinze-Greenberg (Docomomo Journal, 2022)
In 1939, when Tel Aviv had just turned thirty and the building of the White City was in full swing, a woman, most beautiful, came up with an idea for a book: "Tel Aviv. A City's Dramatic Story.” The woman was architect Eric Mendelsohn's wife Louise, and she shared her idea with him and with Yaacov Shiffman,  Tel Aviv's city engineer at the time. Both men were enthusiastic about the idea, and planned initial sessions "to discuss the writing up of the story of Tel Aviv.”